Dysmorphic neurons as cellular source for phase-amplitude coupling in Focal Cortical Dysplasia Type II. Issue 3 (March 2021) - Rampp, Stefan; Rössler, Karl; Hamer, Hajo; Illek, Margit; Buchfelder, Michael; Doerfler, Arnd; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Koelble, Konrad; Peixoto-Santos, Jose Eduardo; Blümcke, Ingmar; et al.
Highlights: New protocol to co-register surgical brain samples with invasive EEG in patients with Focal Cortical Dysplasia (FCD) type II. Seizure onset, spikes, fast gamma oscillations and theta-gamma phase-amplitude-coupling were related to areas with dysmorphic neurons. Despite disorganized distribution of FCD, dysmorphic neurons showed significant phase-amplitude coupling, suggesting persisting anatomical connectivity. Abstract: Objective: Reliable localization of the epileptogenic zone is necessary for successful epilepsy surgery. Neurophysiological biomarkers include ictal onsets and interictal spikes. Furthermore, the epileptic network shows oscillations with potential localization value and pathomechanistic implications. The cellular origin of such markers in invasive EEG in vivo remains to be clarified. Methods: In the presented pilot study, surgical brain samples and invasive EEG recordings of seven patients with surgically treated Focal Cortical Dysplasia (FCD) type II were coregistered using a novel protocol. Dysmorphic neurons and balloon cells were immunohistochemically quantified. Evaluated markers included seizure onset, spikes, and oscillatory activity in delta, theta, gamma and ripple frequency bands, as well as sample entropy and phase-amplitude coupling between delta, theta, alpha and beta phase and gamma amplitude. Results: Correlations between histopathology and neurophysiology provided evidence for a contribution of dysmorphic neurons to interictal spikes, fast gamma activity and ripples. Furthermore, seizure onset and phase-amplitude coupling in areas with dysmorphic neurons suggests preserved connectivity is related to seizure initiation. Balloon cells showed no association. Conclusions: Phase-amplitude coupling, spikes, fast gamma and ripples are related to the density of dysmorphic neurons and localize the seizure onset zone. Significance: The results of our pilot study provide a new powerful tool to address the cellular source of abnormal neurophysiology signals to leverage current and novel biomarkers for the localization of epileptic activity in the human brain.